2003
DOI: 10.1016/s0885-3924(03)00287-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired communication capacity and agitated delirium in the final week of terminally ill cancer patients: prevalence and identification of research focus

Abstract: The maintenance of intellectual activity is an important area in the "good death" concept. To clarify the communication capacity levels of terminally ill cancer patients in their final week, and to identify factors contributing to the development of communication capacity impairment and agitated delirium, a retrospective study was performed on 284 consecutive hospice inpatients. The data were collected by chart review, and two independent raters measured the degree of communication capacity and agitation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 34 publications
4
51
0
1
Order By: Relevance
“…We identified agitated delirium in patients when the score on item 9 of the MDAS was 2 or more and it showed diurnal 1 Graduate School of Pharmaceutical Science, 2 Department of Palliative Medicine, 3 variation. Patients were divided into the agitated delirium and nonagitated delirium groups.…”
Section: Identification Of Patients With Agitated Delirium From Medicmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified agitated delirium in patients when the score on item 9 of the MDAS was 2 or more and it showed diurnal 1 Graduate School of Pharmaceutical Science, 2 Department of Palliative Medicine, 3 variation. Patients were divided into the agitated delirium and nonagitated delirium groups.…”
Section: Identification Of Patients With Agitated Delirium From Medicmentioning
confidence: 99%
“…2 According to a report, agitated delirium was considered present when patients had scores of 2 or 3 on the psychomotor activity item of the Memorial Delirium Assessment Scale (MDAS) any day during the patient's final week. 3 In this study, we conducted a retrospective chart review of terminal patients with cancer who had agitated delirium at an acute care hospital during their last 3 months before death. We took the necessary measures such as maintaining the anonymity of the patients while presenting their data in order to conduct this study in accordance with the Osaka University Hospital Code of Ethics.…”
mentioning
confidence: 99%
“…It seems to be even lower than 20% in different European countries independent of the detailed legal situation [7,8,9,10,11,12]. In cancer patients, early AD consultations are of particular importance due to the imminent risk of impaired consciousness in advanced cases [13,14,15,16,17,18,19,20]. Recent studies showed that ADs improve the process of dying by reducing the patient's fear, the stress on relatives [21], and the physician's risk of burnout [22].…”
Section: Introductionmentioning
confidence: 99%
“…Often when these difficult decisions and clinical transitions are needed, the patient is quite sick and lacks the capacity to participate in end-of-life decision-making. [11][12][13] In these situations, physicians and surrogate decision makers may not be aware of patient preferences, making decisions more difficult. 14,15 Some findings suggest that the withholding and withdrawal of life-sustaining therapies is correlated with physician predictions of survival.…”
mentioning
confidence: 99%